The Importance of Work Motivation and Discipline on the Performance of MSME Employees Photocopy Rofik Karawang - Muhammad Noval Hermawan; Santi Pertiwi Hari Sandi (Formosa Journal of Applied Sciences, 2023)
ABSTRAK Rofik photocopy UMKM is one of the UMKM in the city of Karawang. This observation is concentrated on printing and photocopying which has a vision of becoming the largest printing and photocopying company in the city of Karawang. This observation was carried out to determine the effect of work motivation and work discipline on employee performance in UMKM Copy Rofik which has been operational since 2014. The observation was carried out because researchers considered it necessary to know the effect of the variables studied during a pandemic so as to prepare good human resources for business progress UMKM Copy of Rofik. In an effort to create employee work performance at the Rofik Photocopy MSME, it seems that there are still many obstacles that are faced making it difficult to achieve organizational goals.